PELESTARIAN DAN PERAN MASYARAKAT DI KAWASAN SEKITAR SITU CISANTI - Diana, Dian; Pasya, Gurniwan Kamil (Jurnal Pendidikan Geografi Gea, 2015)
The Around Zone of Situ Cisanti is in the arboretum 73 upstream of Ci Tarum River, there are seven springs that drain the water into Situ Cisanti. However, if the around zone destructively altered, there will be kiln drying of the springs. The purpose of this research are to determine the type of local wisdom that are still made by the society, to determine the distribution of zoning to reduce the pressure of population in protecting areas of land use, to determine the role of reformer agencies and society and the outcome of the efforts to preserve the around zone of Situ Cisanti, and to determine the implications of the research product in conservation and the role of society of Situ Cisanti region in learning Geography in SMA (High School)/ MA / equal. The method of the research is qualitative-verification through phenomenological approach, to seek and uncover the meaning behind the facts found. Even though the destructive activities in the forest of the around zone of Situ Cisanti almost happen in the case, there are still local wisdom in the society. Zoning the around zone of the lake is determined based on the slope and the distance that divided into six zones, with the three functions; the green zone, cultivation zone, and interaction zone. The struggle of change agents and the society can be inspiration for the students to understand, conscious, care, and take action to preserve the environment, so it appears change agent of environmental. The results of this study can be instructional materials for learning in school are expected to make the learner friendly to the environment.